PENDAMPINGAN PEMBUATAN SITE PLAN KOMPLEKS EDUWISATA MUHAMMADIYAH PEJAWARAN BANJARNEGARA - Pinta Astuti; Adhitya Yoga Purnama (LPPM Universitas Abdurrab, 2022)
Istana Qur’an is a modern Muhammadiyah Islamic Boarding School in Sarwodadi Village, Pejawaran District, Banjarnegara, Central Java Province. The boarding school is one of the charities supported by the Pejawaran Muhammadiyah Branch (PCM Pejawaran), as a partner in this community service project. Based on its geographical location, the location of this Islamic boarding school is close to the Dieng tourist area, Banjarnegara so that it can be used as a buffer tourist destination in the Dieng area. In addition, there is no Muhammadiyah site that has been seriously developed into an edu-tourism area even though this Sarwodadi Village has potential, namely the existence of a developed Muhammadiyah Islamic boarding school. Therefore, the purpose of this community service activity is to empower partners in the form of assistance in the preparation of a Muhammadiyah edu-tourism site plan according to technical rules applicable in Indonesia and pay attention to land use and the environment for edu-tourism. Activities carried out in the form of aerial photo surveys with drone maps, Forum Group Discussions (FGD), and technical drawings using CAD-based programs. All activities went well and based on the results of the evaluation, this community service could increase the knowledge of partners from 10% to 100% after the completion of the edu-tourism site plan.